SARS-CoV-2 testing and sequencing for international arrivals reveals significant cross border transmission of high risk variants into the United Kingdom. (August 2021) - Williams, Gareth H; Llewelyn, Alexander; Brandao, Ruben; Chowdhary, Kaiya; Hardisty, Keeda-Marie; Loddo, Marco
Abstract: Background: Mandatory Day 2 and Day 8 PCR testing and variant sequencing of international arrivals has been recently introduced by the UK Government to mitigate against cross-border transmission of high-risk SARS-CoV-2 variants. Methods: SARS-CoV-2 testing and sequencing combines TaqPath CE-IVD COVID-19 RT-PCR with Ion AmpliSeq SARS-CoV-2 Next Generation Sequencing Assay. Retrospective analysis of test trending data was performed from initiation of testing on the 11th March through to the 14th April 2021. Findings: During this time interval, 203, 065 SARS-CoV-2 PCR tests were performed, with 3, 855 samples testing positive, giving a prevalence of 1.9%. In total 1, 913 SARS-CoV-2 genomes were sequenced from positive cases with Ct values < 30 and 1, 635 (85.5%) sequences passed quality metrics for lineage analysis. A high diversity of 49 different SARS-CoV-2 variants were identified, including the VOCs B.1.1.7 (Kent; 80.6%), B.1.351 (South Africa; 4.2%), B.1.617.2 (India; 1.7%), P.1 (Brazil; 0.4%) and B.1.1.7 with E484K (Bristol; 0.2%). Vaccine effectiveness was age-related and dose-dependent, ranging from 5% in > 60 with a single dose to 83% in <60 with both doses of a vaccine. Viral load was variant dependent with the B.1.617.2 showing a 21 fold increase in viral copy number compared to the other variants. Interpretation: The unexpectedly high prevalence of COVID-19 infection in UK arrivals is associated with a rich diversity of SARS-CoV-2 high risk variants entering the UK including the VOC B.1.617.2. Vaccination does not preclude infection and its effectiveness is significantly age-dependent and impacted by variant type. The rapid high-throughput test and sequence workflow we have adopted is particularly suited to the monitoring of cross border transmission and enables immediate public health interventions. Funding: Data analysis conducted in this study was limited to secondary use of information previously collected in the course of normal care.